Papua New Guinea Financial Consumer Protection Diagnostic 2018 - International Finance Corporation (International Finance Corporation, Washington, DC, 2018)
The objective of the diagnostic review of financial consumer protection in PNG was to assess the FCP legal and regulatory framework and industry practices relevant to key parts of the regulated PNG financial sector. The diagnostic specifically considers the banking, non-bank financial institutions (NBFI), insurance, and payments sectors. Preliminary consideration has also been given to the superannuation sector and the securities, investments and informal sectors are not within the scope of this review. The review was conducted based on the revised and enhanced 2017 World Bank Good Practices for Financial Consumer Protection and the G20 High – Level Principles on Financial Consumer Protection and Digital Financial Inclusion. Regard has also been had to the Better Than Cash Alliance Responsible Digital Payments Guidelines. The following topics have been covered: (i) legal and regulatory framework; (ii) FCP supervision and capacity; (iii) transparency and fair treatment; and (iv) consumer complaints. A broad variety of stakeholders were consulted for the purposes of this diagnostic review, including government entities and regulators, representatives of the banking, NBFI, insurance and payments sectors and industry associations. The report was prepared as part of the PNG Financial Consumer Protection Project, funded by the Department of Foreign Affairs in Australia and the Ministry of Foreign Affairs in New Zealand under the PNG Partnership.